Responses of Bovine WC1(+) γδ T Cells to Protein and Nonprotein Antigens of Mycobacterium bovis - Welsh, Michael D. (American Society for Microbiology, 2002)
WC1(+) γδ T cells of Mycobacterium bovis-infected cattle are highly responsive to M. bovis sonic extract (MBSE). In mycobacterial infections of other species, γδ T cells have been shown to respond to protein and nonprotein antigens, but the bovine WC1(+) γδ T-cell antigenic targets within MBSE require further definition in terms of the dominance of protein versus nonprotein components. The present study sought to characterize the WC1(+) γδ T-cell antigenic targets, together with the role of interleukin-2 (IL-2), in the context of M. bovis infection. This was achieved by testing crude and defined antigens to assess protein versus nonprotein recognition by WC1(+) γδ T cells in comparison with CD4(+) αβ T cells. Both cell types proliferated strongly in response to MBSE, with CD4(+) T cells being the major producers of gamma interferon (IFN-γ). However, enzymatic digestion of the protein in MBSE removed its ability to stimulate CD4(+) T-cell responses, whereas some WC1(+) γδ T-cell proliferation remained. The most antigenic protein inducing proliferation and IFN-γ secretion in WC1(+) γδ T-cell cultures was found to be ESAT-6, which is a potential novel diagnostic reagent and vaccine candidate. In addition, WC1(+) γδ T-cell proliferation was observed in response to stimulation with prenyl pyrophosphate antigens (isopentenyl pyrophosphate and monomethyl phosphate). High levels of cellular activation (CD25 expression) resulted from MBSE stimulation of WC1(+) γδ T cells from infected animals. A similar degree of activation was induced by IL-2 alone, but for WC1(+) γδ T-cell division IL-2 was found to act only as a costimulatory signal, enhancing antigen-driven responses. Overall, the data indicate that protein antigens are important stimulators of WC1(+) γδ T-cell proliferation and IFN-γ secretion in M. bovis infection, with nonprotein antigens inducing significant proliferation. These findings have important implications for diagnostic and vaccine development.